AUDITOR SWITCHING AND AUDIT TENURE ON AUDIT QUALITY, FEE AUDIT ON THE INDONESIA STOCK EXCHANGE - Majid, Jamaluddin; Ratnasari, Ratnasari; Tabe, Ridwan (Program Study Islamic Banking, Faculty of Economics and Bussiness Islam, State Islamic Institute of Manado (IAIN) Manado, 2021)
The research was aimed to determine the effect of auditor switching, audit tenure, company size variables on audit quality and to determine fee audit fee variables in moderating the effect between auditor switching, audit tenure, and company size variables on audit quality. The population is manufacturing companies listed on the Indonesia Stock Exchange during the 2014-2017 period. The total sample is 43 companies using the purposive sampling technique. The data used in the research were financial statements. The method of data analysis uses logistic regression analysis for the hypotheses of auditor switching, audit tenure, and company size. Logistic regression analysis with a residual test for the hypotheses of auditor switching, audit tenure, and company size on audit quality that moderated by fee audit. The results of the research indicated that auditor switching had a negative and significant effect on audit quality. While audit tenure and company size have a positive and significant effect on audit quality. Related to moderating variables indicate that fee audit is not able to moderate auditor switching and audit tenure on audit quality. Conversely, fee audit has an effect as a moderating variable between company size and audit quality